Organic transistors fabricated by contact coating at liquid-solid interface for nano-structures - Yu-Wen Cheng; Chao-Hsuan Chen; Hsin-Fei Meng; Hsiao-Wen Zan; Yu-Chiang Chao; Sheng-Fu Horng (AIP Advances, 2015)
A contact coating method is developed to cover the nano-channels with 100 nm or 200 nm diameter and 400 nm depth with a poly(4-vinylphenol) (PVP). In such coating the nano-channels faces downwards and its vertical position is controlled by a motor. The surface is first lowered to be in immediate contact with the polyvinylpyrrolidone (PVPY) water solution with concentration from 1 to 5 wt%, then pulled at the speed of 0.004 to 0.4 mm/s. By tuning the pulling speed and concentration we can realize conformal, filled, top-only, as well as floating film morphology. For a reproducible liquid detachment from the solid, the sample has a small tilt angle of 3 degree. Contact coating is used to cover the Al grid base of the vertical space-charge-limited transistor with PVPY. Poly(3-hexylthiophene-2,5-diyl) (P3HT) as the semiconductor. The transistor breakdown voltage is raised due to base coverage achieved by contact coating.